Characterization of physiological and antioxidant responses in Run1Ren1 Vitis vinifera plants during Erysiphe necator attack - Sosa-Zuniga, Viviana; Martínez-Barradas, Vera; Espinoza, Carmen; Tighe-Neira, Ricardo; Valenzuela, Álvaro Vidal; Inostroza-Blancheteau, Claudio; Arce-Johnson, Patricio (Frontiers in Plant Science, 2022)
One of the most important fruit crops worldwide is the grapevine. Fungal attacks threaten its yield and fruit quality. One of the most harmful fungal diseases is powdery mildew, affecting plant physiology and metabolism. Incorporating resistance genes such as Run1 and Ren1 in the new vine selections offers a sustainable alternative to control the disease. These combined genes produce an immune response that prevents the development of the disease. So far, it has not been studied whether this response generates alterations in the physiological parameters of resistant plants in the presence of the fungus or if it has an associated energy cost. For that reason, the main goal of our research was to determine if Run1Ren1 plants presented alterations in their physiological parameters in the presence of the fungus. To achieve this target, we evaluated the net photosynthesis rate, the level of photosynthetic pigments (chlorophyll-a and carotenoids), the gas exchange (transpiration and stomatal conductance), and the oxidative parameters (MDA, antioxidant activity, and phenols). We used a previously characterized resistant Run1Ren1 genotype and the susceptible Carménère cultivar for the measurements. Our results showed that the physiological parameters of Run1Ren1 plants were not negatively affected by the fungus at 10 dpi, unlike what happened with the susceptible plants. Therefore, we proposed that the resistant response triggered by Run1Ren1 gives a physiological advantage to grapevines by preventing the development of powdery mildew infection without an energy cost associated with the studied conditions.